Carbon assimilation, herbage accumulation, nutritive value, and grazing efficiency of Mulato II brachiariagrass under continuous stocking - Silva, Valdson José da (2016)
Grazed pastures are the backbone of the Brazilian livestock industry and grasses of the genus Brachiaria (syn. Urochloa) are some of most used tropical forages in the country. Although the dependence on the forage resource is high, grazing management is often empirical and based on broad and non-specific guidelines. Mulato II brachiariagrass (Convert HD 364, Dow AgroSciences, São Paulo, Brazil) (B. brizantha × B. ruziziensis × B. decumbens), a new Brachiaria hybrid, was released as an option for a broad range of environmental conditions. There is no scientific information on specific management practices for Mulato II under continuous stocking in Brazil. The objectives of this research were to describe and explain variations in carbon assimilation, herbage accumulation (HA), plant-part accumulation, nutritive value, and grazing efficiency (GE) of Mulato II brachiariagrass as affected by canopy height and growth rate, the latter imposed by N fertilization rate, under continuous stocking. An experiment was carried out in Piracicaba, SP, Brazil, during two summer grazing seasons. The experimental design was a randomized complete block, with a 3 x 2 factorial arrangement, corresponding to three steady-state canopy heights (10, 25 and 40 cm) maintained by mimicked continuous stocking and two growth rates (imposed as 50 and 250 kg N ha-1 yr-1), with three replications. There were no height × N rate interactions for most of the responses studied. The HA of Mulato II increased linearly (8640 to 13400 kg DM ha-1 yr-1), the in vitro digestible organic matter (IVDOM) decreased linearly (652 to 586 g kg-1), and the GE decreased (65 to 44%) as canopy height increased. Thus, although GE and IVDOM were greatest at 10 cm height, HA was 36% less for the 10- than for the 40-cm height. The leaf carbon assimilation was greater for the shortest canopy (10 cm), but canopy assimilation was less than in taller canopies, likely a result of less leaf area index (LAI). The reductions in HA, plant-part accumulation, and LAI, were not associated with other signs of stand deterioration. Leaf was the main plant-part accumulated, at a rate that increased from 70 to 100 kg DM ha-1 d-1 as canopy height increased from 10 to 40 cm. Mulato II was less productive (7940 vs. 13380 kg ha-1 yr-1) and had lesser IVDOM (581 vs. 652 g kg-1) at the lower N rate. The increase in N rate affected plant growth, increasing carbon assimilation, LAI, rates of plant-part accumulation (leaf, stem, and dead), and HA. The results indicate that the increase in the rate of dead material accumulation due to more N applied is a result of overall increase in the accumulation rates of all plant-parts. Taller canopies (25 or 40 cm) are advantageous for herbage accumulation of Mulato II, but nutritive value and GE was greater for 25 cm, suggesting that maintaining ∼25-cm canopy height is optimal for continuously stocked Mulato II.